Analysis Constumer of Continuity of Mobile Loans and Payments for Akulaku Fintech Services Using TAM - Arfian, Andi; Siregar, Juarmi; Ambar Wasesha, Dian (Technologia : Jurnal Ilmiah, 2024)
The aim of this research is to determine the factors that influence the re-acceptance of the Akulaku Payment Online Fintech System using the Technology Accept Model. This research model directly follows the study using variables namely Perceived Usefulness, Perceived Ease of Use, Convenience, Security, Service quality and Continuance intention as independent variables. variable. dependent Information was collected using the questionnaire method with a total of 65 respondents and sent directly to the respondents. Data were analyzed using the TAM Model and PLS method. The results of this research show that the factors that directly influence the acceptance of the Akulaku Fintech System are perceived Service quality and Continuance intention which are defined as variables that have a positive value or have a significant relationship, namely Perceived Ease of Use, Convenience, Security, which show a significant influence on the Continuance intention variable and only There is one variable that is not significant with the Continuance Intention variable, namely the Perceived Usefulness variable. Based on the results of the impact analysis on the research variables, it shows that the results of the perception data analysis of Perceived Usefulness have an insignificant impact on Continuance intention, Akulaku Fintech online with a T statistical result of 1,409 (>1.96). shows that the relationship is negative with this research, namely rejecting hypothesis H2. This can be explained by the fact that although the Fintech company Akulaku considers the application easy to understand and use, some respondents feel that the ease of use of the existing online Fintech payment system can still be improved, especially in the benefits aspect.Keywords: Fintech, Online Payment, TAM, Akulaku